Aquaculture from inland fish cultivation to wastewater treatment: a review - Abdurahman Hafez Mohammed Kashem (17787551) (2023)
The aquaculture industry is rapidly developing, generating a high amount of wastewater. Inland aquaculture effluents contain nutrients and other substances that can cause eutrophication and the emergence of resistive organisms if released into the environment. Hence, aquaculture wastewater should be treated appropriately for reuse in different applications or safely released into the environment, promoting a sustainable industry and a circular economy. The current review provides insight into aquaculture wastewater generation, constituents, and treatment through various technologies. This study’s treatment technologies could be classified as physical, chemical, and biological. SWOT analysis was conducted on each technology to provide an in-depth understanding of the advantages and drawbacks. Suggestions were also stated to shed light on the importance of a sustainable aquaculture industry and the means to transition toward a circular economy. Other Information Published in: Reviews in Environmental Science and Bio/Technology License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s11157-023-09672-1